Analisis hukum Islam terhadap pengembangan wakaf berbasis sukuk untuk pemberdayaan tanah yang tidak produktif di Indonesia - Siska Lis Sulistiani (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2018)
Abstract. Waqf has more flexibility than zakat so that the form of waqf will continue to grow in accordance with the times. The development of the waqf must still be in the corridor of the Shari'a so that the value of ubudiyah and iqtishadiyah remain. The potential of waqf land in Indonesia is so large, making the number of unproductive waqf land due to limited aspects of funding and management. Sukuk-based waqf innovation launched in early 2017 by the Government in order to maximize the potential of waqf land in Indonesia, only the legal aspects of sukuk itself are legally still legitimate. The methodology used is qualitative research methods through literature study, with normative juridical research types and secondary data sources collected by documentary and interview methods and analyzed descriptively qualitatively so that the level of synchronization and feasibility of norms is known. The results of this study are that waqf and sukuk stand from 2 different contract goals, namely tabarru and tijaroh contracts, which are combined in order to bring greater value to benefit. The position of the sukuk-based waqf law if it is built on the contract of sukuk ijarah which is almost similar to bai al-wafa according to the jumhur ulama is prohibited, except for Hanafi schools that allow it. This is in line with the DSN fatwa regarding sukuk and Article 112-113 of the KHES regarding Bai al-Wafa. Apart from differences of opinion in the context of fiqh, it is necessary to pay attention to the clear regulatory aspects that underlie sukuk-based waqf, pay attention to the administration of waqf assets both land and building certificates and waqf certificates and attention to sharia legality aspects so that the main purpose of waqf for the benefit of the people can still achieved without reducing the value or the form of waqf assetsAbstrak. Wakaf memiliki fleksibilitas yang lebih dibandingkan zakat sehingga bentuk wakaf akan terus berkembang sesuai dengan perkembangan zaman. Perkembangan wakaf tersebut tetap harus dalam koridor syariat sehingga nilai ubudiyah dan iqtishadiyah nya tetap ada. Potensi tanah wakaf di Indonesia yang begitu besar, menjadikan banyaknya tanah wakaf yang tidak produktif diakibatkan terbatasnya aspek pendanaan dan manajemen. Inovasi wakaf berbasis sukuk yang diluncurkan di awal 2017 oleh Pemerintah dalam rangka memaximalkan potensi tanah wakaf di Indonesia, hanya saja aspek hukum sukuk itu sendiri secara hukum masih khilafiah. Metodologi yang digunakan adalah metode penelitian kualitatif melalui studi kepustakaan, dengan jenis penelitian yuridis normatif dan sumber data sekunder yang dikumpulkan dengan metode dokumenter dan wawancara lalu dianalisis secara deskriptif kualitatif sehingga diketahui taraf sikronisasi dan kelayakan norma. Hasil penelitian ini bahwa wakaf dan sukuk berdiri dari 2 tujuan akad yang berbeda yaitu akad tabarru dan tijaroh, yang digabungkan dalam rangka menghadirkan nilai maslahat yang lebih besar. Kedudukan hukum wakaf berbasis sukuk ini jika dibangun diatas akad sukuk ijarah yang hampir serupa bai al-wafa  menurut jumhur ulama diharamkan, kecuali madzhab hanafi yang membolehkannya. Hal ini yang selaras dengan fatwa DSN tentang sukuk dan Pasal 112-113 KHES tentang bai al-wafa. Terlepas dari perbedaan pendapat dalam konteks fiqh ini, perlu diperhatikan aspek regulasi yang jelas yang melandasi wakaf berbasis sukuk ini, memperhatikan perapihan administrasi aset wakaf baik sertifikat tanah dan bangunan maupun sertifikat wakaf dan perlu diperhatikan aspek legalitas syariah agar tujuan utama wakaf untuk kemaslahatan umat tetap dapat tercapai tanpa mengurasi nilai ataupun wujud dari asset wakaf.